Relasi Aktor dalam Kebijakan Halal Tourism di Kabupaten Maros - Aisyah Mujahida Ahmad, Andi; Sukri; ., Haryanto (JPP (Jurnal Politik Profetik), 2023)
This article aims to describe the relationship between actors to find the political aspects of halal tourism policies that are a trend in local government policies in Indonesia today. This article uses the Advocacy Coalition Framework (ACF) approach to analyze the position of each policy actor in the formulation of policies on halal tourism in the Maros Regency. The research method uses descriptive qualitative analysis by describing the relationship of policy actors both formally and informally in the formulation of the Draft Regional Regulation on Halal Tourism in the Maros Regency and seeing the interactions that influence the policy process. The results showed that the actors involved in halal tourism policy were divided into two groups: state actors and non-state actors. These policy actors interact with each other, involving different interests. However, the tendency that occurs leads to dependence on state actors. The interaction of these actors results in a coalition of pros and cons, which could weaken the implementation of halal tourism policies. This article contributes to expanding insights in the study of interactions between policy actors involving different interests in halal tourism policy in Indonesia.